PENGARUH SELF EFFICACY DAN KREATIFITAS TERHADAP MINAT WIRAUSAHA DI INDONESIA - Nur Kholifah, Nuzulia; Saefullah Zevender, Poy; Zaenal Mustofa, Taufiq (LPPM STKIP Pangeran Dharma Kusuma Segeran Juntinyuat Indramayu, 2024)
The literature review study was motivated by empirical events that illustrate the increasing number of open unemployment as well as the lack of interest in entrepreneurship among Indonesian people. The literature review study method was carried out by reviewing seven articles obtained from several sources including Google School and e-resources. The article search strategy used available databases. on e-resources, one of which is Google Schoolar with the keywords used in searching for journals, namely: self-efficacy, creativity, interest, entrepreneurship. Researchers use the word